METHODOLOGICAL APPROACHES TO FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE TECHNICAL AND TECHNOLOGICAL SPECIALISTS IN AGRICULTURAL COLLEGES - Stadniichuk, Iryna (Professional Pedagogics, 2019)
Rеlevance: the need to justify the methodological foundations for the future professional competence of electrical technicians is determined by the needs of qualified specialists in the agricultural sector.The purpose of the study is to substantiate methodological principles, to specify and to cover the scientific approaches to the formation of professional competence of future electrical technicians in agricultural colleges.Methods: theoretical research methods: analysis of psychological and pedagogical literature on the problem – to identify the state of the problem under study in pedagogical theory and practice; analysis, synthesis, abstraction, generalization – for substantiation of methodological bases of formation of professional competence of future electrical technicians.Results. The article highlights a number of methodological approaches, such as: systematic, competent, humanistic, cultural, axiological, personality-oriented, activity-developmental, environmental, information, integration, technological, synergistic approaches, which it is expedient to rely on in the process of analysis of professional competence of future specialists of technical and technological specialties in agricultural colleges. The content and essence of these approaches are considered. This made it possible to set the basic requirements for the formation of professional competence of future electrical technicians and understanding of the construc- tion of the educational process in the higher school for the preparation of these specialists.Conclusions: the methodological principles for the future professional competence of electrical technicians should be based on the unity of such basic scientific approaches as competent, personality-oriented, activity-developmental, humanistic, cultural, axiological, informational, and, to a lesser degree, synergistic approaches.
Keywords: methodological approach; professional competence; future electrical technician; agricultural college